Entrepreneurs with high expectations of growth and economic growth (Dimensión Empresarial, 2018)
This article explains the impact of entrepreneurs’ expectations on countries economic growth, considering the public policies that foster the development. Using data from Global Entrepreneurship Monitor and the World Economic Forum a descriptive analysis is done, then with the application of ordinary least squares (OLS) the effects are explained by groups of countries: efficiency-driven and innovation-driven. Ultimately in innovation-driven countries is clear the relationship between expectations of entrepreneurs and economic growth, while, with some exceptions, in efficiency-driven countries public policy should be focused on break the barrier that halt the momentum of entrepreneurs with high expectations.
Keywords: Entrepreneurship; public policies; competitiveness; growth expectations.